Nutrition and Performance in Sport : Science at the Tip of the Fork - Christophe Hausswirth (INSEP-Éditions, 2015)
How to recover properly with food? How to eat during a trip abroad or during a training course in altitude? What to do to preserve your bone health? How to conciliate the ramadan and the training? How to lose weight cleverly? What sugars? What proteins?... As regards nutrition, athletes and their coaches ask themselves a lot of questions, and each of them deserves a clear answer! This is the main objective of this book, which gathered the world's greatest specialists of sports nutrition in order to bring the eagerly expected answers... Indeed, when the competition is tighter than ever, empiricism is no longer enough: the victory, which always depends on minute subtleties, requires rational choices, especially regarding food. And if sports victory is a legitimate aim, it should not be pursued at the expense of health: even today, athletes still put it at stake. Thereby, this is the second objective of this book: learning how to conciliate performance and body respect...